Modes of staff development [videorecording] (Quezon City SEAMEO INNOTECH)
Demonstrated the various modes to upgrade school head instructional and management/leadership skills. Describes the steps involved in starting and/or reviewing different modes of staff development specifically to enable school heads to help improve the personal and professional development of their teachers.
VHS.
Host, Lia Andanar.
Keywords: School principals -- Training of; School management and organization; School personnel management